2016
DOI: 10.1111/jwas.12279
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of Biofouling on Offshore Mussel Farms

Abstract: Biofouling is a significant operational problem for the aquaculture industry globally; however, options for on-farm management are limited. In New Zealand, the green-lipped mussel, Perna canaliculus, has historically been cultivated at inshore locations, but increased competition for space has led the industry to develop offshore farming sites several kilometers from the coast. We hypothesize that the distance to these farm sites from coastal locations, and their placement over extensive soft-sediment habitats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Therefore increase of shipping-related pressures can be anticipated as well. Moreover, addition of artificial substrates can favor the establishment of non-indigenous species and serve as a reservoir or stepping-stone for their further spread (Tyrell and Byers, 2007;Mineur et al, 2012;Atalah et al, 2016). Such interlinkage of drivers, pressures and impacts should be taken into consideration when designing the response strategies.…”
Section: Example 3: Constructionsmentioning
confidence: 98%
“…Therefore increase of shipping-related pressures can be anticipated as well. Moreover, addition of artificial substrates can favor the establishment of non-indigenous species and serve as a reservoir or stepping-stone for their further spread (Tyrell and Byers, 2007;Mineur et al, 2012;Atalah et al, 2016). Such interlinkage of drivers, pressures and impacts should be taken into consideration when designing the response strategies.…”
Section: Example 3: Constructionsmentioning
confidence: 98%
“…), which can be partly attributed to a lack of some of their natural predators in floating structures 274 . Another potential advantage comes from locating farms further from the coast, where short‐dispersing coastal organisms cannot reach, as is the case of ascidians 275 . The benefits of strong currents and the low connectivity with coastal organisms will need to be studied on a local basis, as the prevention of the settlement by some organisms may lead to reduced competition for more damaging biofouling species, depending on the communities that are present in the region.…”
Section: Operational Considerationsmentioning
confidence: 99%
“…Favorable features of open ocean waters include ample space for expansion, tremendous carrying and assimilative capacity, reduced conflict with many user groups, lower exposure to human sources of pollution, the potential to reduce some of the negative environmental impacts of coastal fish farming, and optimal environmental conditions for a wide variety of marine species, to name a few (Buck 2002(Buck , 2004Ryan 2004;Langan 2007;Langan and Horton 2003;Ostrowski and Helsley 2003;Helsley and Kim 2005;Benetti et al 2006;Howell et al 2006;Ward et al 2006). A recent study conducted in New Zealand indicated an additional benefit that open ocean locations may be subjected to less biofouling (Atalah et al 2016), a costly maintenance operation for coastal aquaculture. Those features, coupled with advances in farming technology (Fredheim and Langan 2009) would seem to present an excellent opportunity for growth, however, development in offshore waters has been limited.…”
Section: Moving Aquaculture Operations Offshorementioning
confidence: 99%